Estratégias para gestão de pessoas e economia solidária: o estudo da Cooperativa de Trabalho dos Catadores de Material Reaproveitável de Rio Claro - SP - Lima, Valdemir dos Santos de (Universidade Federal de São Carlos, 2013)
The performance of the capitalist system, associated with urban areas, has contributed to the growth of solid waste scattered in urban centers of towns and cities, consisting mainly of materials that can be recycled. The generation of waste has assumed proportions that make this issue a major concern of any government, triggering several actions pertaining to the theme. One of the actions taken by the Rio Claro / SP was the creation of a Cooperative Collectors of Recyclable Material - COOPERVIVA, aiming to reduce the environmental impact generated by this waste and ensure an increase in the useful life of the county landfill, strengthening collective work through the Solidarity Economy and actions for Environmental Education. The actions developed by the cooperative have allowed the insertion of new collectors and increasing demand for recyclable waste collected by the cooperative. The need for collective management, aiming at personal development, the process of collective work of the group, the conditions for educated individuals and their relationship with the local government set up the goal of this work, which aims to propose management strategies more effective in daily life of each member, providing them with a work environment in a more differentiated and solidarity in order to provide an economic benefit and social practices with recognition and importance of the work that each member has developed in the city.
Keywords: Resíduos sólidos; Gestão de pessoas; Cooperativas de catadores; Economia solidária; Coleta seletiva; People management; Pickers cooperative; Solidarity economy; Solid waste; ENGENHARIAS::ENGENHARIA SANITARIA